Effect of sodium taurodeoxycholate on PEO-PPO-PEO triblock copolymer F127 with incorporated SNAP: Insights into micellization, gelation, and nitric oxide release - Bomediano, Mateus P.; Plivelic, Tomás S.; Pedersen, Jan Skov; Galantini, Luciano; Schillén, Karin ; 0000-0001-8147-1733; de Oliveira, Marcelo G. (Colloids and Surfaces A: Physicochemical and Engineering Aspects, 2026)
We report the first incorporation of S-nitroso-N-acetylpenicillamine (SNAP) into micellar systems of the poly(ethylene oxide)-poly(propylene oxide)-poly(ethylene oxide) (PEO-PPO-PEO) triblock copolymer Pluronic® F127 for nitric oxide (NO) delivery and show how sodium taurodeoxycholate (NaTDC) modulates F127 micellization and gelation. Using differential scanning calorimetry, small-angle X-ray scattering, rheology, dynamic light scattering, UV–vis spectroscopy, and chemiluminescence NO analysis, we identify two NaTDC-dependent regimes. At low NaTDC/F127 ratios (MR ≤ ∼1.2), NaTDC associates with F127 micelles, lowering the critical micellization temperature and modestly compacting the PPO cores. At higher ratios (MR ≥ ∼3.8), micellization becomes less cooperative, small bile salt–rich complexes form, and at 25 wt% F127, the gel nanostructure transitions from face-centered cubic phase to body-centered cubic phase and eventually loses long-range order (MR ∼6.2). SNAP load does not alter micellization, locates at the core–corona interface, and shows enhanced solubility that depends more on F127 concentration than on NaTDC. Thermal NO release from SNAP (25 °C, dark) follows second-order kinetics, slowing as F127 concentration increases (1–25 wt%), resulting in prolonged NO release. These findings contribute to advancing the understanding of the behavior of PEO-PPO-PEO/NaTDC micellar systems, by demonstrating how NaTDC regulates micellization and gelation. Moreover, the finding that F127 concentration controls SNAP stability and NO-release kinetics, makes the F127/NaTDC system a potential modular platform for sustained and localized NO delivery.